Who Will Feed China in the 21st Century? Income Growth and Food Demand and Supply in China - Fukase, Emiko; Martin, Will (World Bank, Washington, DC, 2014)
This paper uses resource-based cereal equivalent measures to explore the evolution of China's demand and supply for food. Although demand for food calories is probably close to its peak level in China, the ongoing dietary shift to animal-based foods, induced by income growth, is likely to impose considerable pressure on agricultural resources. Estimating the relationship between income growth and food demand with data from a wide range of countries, China's demand growth appears to have been broadly similar to the global trend. On the supply side, output of food depends strongly on the productivity growth associated with income growth and on the country's agricultural land endowment, with China appearing to be an out-performer. The analyses of income-consumption-production dynamics suggest that China's current income level falls in the range where consumption growth outstrips production growth, but that the gap is likely to begin to decline as China's population growth and dietary transition slow down. Continued agricultural productivity growth through further investment in research and development, and expansion in farm size and increased mechanization, as well as sustainable management of agricultural resources, are vital for ensuring that it is primarily China that will feed China in the 21st century.